The Influence of Service Quality and Facilities on Customer Satisfaction and its Impact on Revisit Intention (a Study in Milenium Gym Palu) - Sisilya Kalyani Chandra; Agustinus Nugroho (Dinasti Publisher, 2025)
For the past few years, Indonesia has been experiencing significant growth in fitness industry due to higher societal awareness on healthy lifestyle. By 2027, the projected market volume in health and fitness could reach US12.23m. As this industry is getting bigger by years, management needs to acknowledge the significance of service quality and facilities on satisfaction which impact directly on loyalties of the customer. This study employs explanatory research with a quantitative approach. The data collection process is through online questionnaire distribution to the gym members with a minimum of 258 samples. The statement items in the instrument is measured using Likert scale. To analyze the data, this research will use PLS-SEM. The expected finding of this study is to offer new knowledge for the management in the industry on sustaining their business operations in the long run.